Foreign Policy, Islam and Democracy in Indonesia - Dewi Fortuna Anwar (Journal of Indonesian Social Sciences and Humanities, 2010)
The relations between Islam and Democracy in Indonesia and their implications for the country’s foreign policy have attracted considerable attention in recent years. In the early years of his first presidential term, Susilo Bambang Yudhono introduced the concept of Indonesia’s international identity, that is, as a country in which Islam, democracy and modernity go hand in hand. In the post-9/11 international context, in which perceptions of Islam are largely negative, Indonesia’s special attributes as the largest Muslim-majority country and the world’s third largest democracy have special values. The international community, especially Western countries, has looked to Indonesia to provide an alternative face of Islam in the midst of rising religious extremism and terrorism. Indonesia, however, still faces many challenges in realising its aspirations to be a bridge between the Islamic world and the West, and as an alternative model within the Islamic world. Frequent acts of religious intolerance have marred Indonesia’s claim as a moderate Islamic force while Indonesia has generally been perceived to lie in the periphery of the Islamic world.